CTNI-28. VOLUMETRIC AND DOSIMETRIC PATTERNS OF FAILURE ANALYSIS OF A PHASE II CLINICAL TRIAL OF 18F-DOPA-PET DIRECTED DOSE ESCALATED RADIOTHERAPY FOR GLIOBLASTOMA. (12th November 2021) - Breen, William; Anderson, S Keith; Pafundi, Deanna; Kaufmann, Timothy; Hunt, Christopher; Lowe, Val; Vogen, Diane; Yan, Elizabeth; Sarkaria, Jann; Brown, Paul; Kizilbash, Sani; Uhm, Joon; et al.
Abstract: While dose escalation of radiotherapy (DERT) has failed to improve overall survival (OS) or progression-free survival (PFS) for glioblastoma in previous studies, a recent phase II clinical trial utilizing 18F-DOPA-PET-directed DERT demonstrated improved PFS in MGMT-unmethylated patients and OS in MGMT-methylated patients compared to historical controls. This planned secondary analysis sought to determine 1) how 18F-DOPA-PET changes RT volumes beyond standard MRI-planning, 2) which patients benefit most and least from this protocol, 3) which are mostly likely to experience clinically significant radionecrosis after DERT, and 4) patterns of failure after DERT. For 69 evaluable patients, median MRI-defined, PET-defined, and combined low-dose gross tumor volumes (GTV51) were 54 cc (range 9-248), 23 cc (0.4-179), and 62 cc (10-260), respectively. Median MRI-defined, PET-defined, and combined high-dose GTVs (GTV76) were 32 cc (range 4-136), 6 cc (0.1-138), and 34 cc (4-162), respectively. 18F-DOPA-PET resulted in a median volumetric expansion of 13% (0-243%) and 5% (0-217%) from MRI-defined low-dose and high-dose GTV's, respectively. Central failures ( >95% of recurrence tumor volume) occurred within the 76 Gy, 60 Gy, and 51 Gy isodose lines in 32 (46%), 60 (87%), and 64 (93%) patients, respectively. Recursive partitioning analysis stratified patients by OS and PFS. Patients with 18F-DOPA-PET-defined GTV76 > 7.8cc, MRI-defined GTV76 > 42.7cc, and MGMT promotor-unmethylated tumors had the shortest OS, while patients with smaller PET and MRI-defined tumors had the longest OS (median 10.4 vs. 64.6 months, p< 0.001). Similarly, PFS was worst in patients with 18F-DOPA-PET-defined GTV76 > 2.17 cc who had biopsy only (median PFS 3.2 months, p< 0.001). Patients with 18F-DOPA-PET-defined GTV51 > 50 cc had the highest risk of grade 3+ radionecrosis (p< 0.001). In conclusion, larger 18F-DOPA-PET and MRI-defined tumor volumes were associated with worse outcomes, and 18F-DOPA-PET-directed DERT appears to reduce risk of central recurrence in high-dose volumes.